Calculation of the Basic Cost of Boarding Rooms Using the Activity Based Costing Method in Determining Boarding Room Rental Rates (Case Study of Boarding Houses in Environment VIII, Bahu Village) - Paraibabo, Medlin Ivana Atalia; Runtu, Treesje; Lintong, Diana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Activity Based Costing is a system of accumulating costs and assigning costs to a product using various cost drivers, carried out by tracing costs from activities and after that tracing costs from activities to a product. The aim of this research is to determine the calculation of the cost of boarding rooms using the Activity Based Costing method in determining boarding room rental rates at boarding houses in Ward VIII, Bahu Village. The data analysis method used in this research is the descriptive analysis method. Based on the research results obtained, the basic price of boarding rooms using the activity based costing method has a nominal difference that is smaller than the price set by the boarding room owner.